Enhancing Integrity among Academicians in Social Media: Exploring Challenges and Management Strategies in the Realm of Digital Era - Nadiah Ramlan; Mohamad Hafizuddin Mohamed Najid; Norsyamlina Che Abdul Rahim; Amzari Abu Bakar (Semarak Ilmu Publishing, 2026)
Tier 4- Non-Indexed Publication